Handover and Care Transitions Training for Internal Medicine Residents - Manuel Eskildsen; Joanna Bonsall; Amy Miller; Ugochi Ohuabunwa; Christina Payne; Eva Rimler; Jason Stein (Association of American Medical Colleges, 2012)
Abstract The presentations and exercises in this resource are intended to serve as introductory training tools for interns and residents for them to better perform care transitions. In this context, care transitions are defined as "the movement patients make between health care practitioners and settings as their condition and care needs change during the course of a chronic or acute illness" (Care Transitions Program, http://caretransitions.org). For our training exercises, we have focused on two types of transitions: handovers of patients between hospital providers, as well as hospital discharges. In this resource, we have two different training experiences offered to internal medicine interns and residents at the Emory University School of Medicine: a two-hour workshop on care transitions issues offered to interns during their initial orientation, as well as an interactive presentation given to all residents a month into the academic year. The enclosed learning materials are part of a comprehensive curriculum for internal medicine interns and residents addressing care transitions in the hospital. It specifically covers handovers of patients in the hospital, as well as issues regarding patient care at discharge. On the first implementation of this curriculum during the 2010-2011 academic year, the interns receiving the initial orientation gave the course a 4.1/5 in terms of perceived effectiveness. Interns' confidence in their ability to perform care transitions tasks improved from 19.8 to 25.7 on a 30-point scale (p<0.0001), and knowledge scores improved from 4.5 to 5.7 out of 8 (p<0.0001), from pre- to post-course. After the course, 79% (34 of 43) answered "agree" or "strongly agree" when asked whether the course played a key role in their ability to hand over patients. 67% (29 of 43) answered "agree" or "strongly agree" when asked the same question about their ability to discharge patients. This was the first dedicated curriculum on handovers or care transitions for medical residents at the Emory University School of Medicine. The lectures and exercises included in this resource are the core of a longitudinal care transitions curriculum that is now part of Emory's internal medicine training program.